The Effect Of Combination Of Progressive Muscle Relaxation And Mckenzie Neck Exercise On Functional Ability In The Case Of Myofascial Pain Syndrome Muscle Upper Trapezius On Students - Kirana Kinantan Kinasih; Safun Rahmanto; Nurul Aini Rahmawati (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2022)
Student activities in front of the computer for too long can be at risk of causing myofascial pain syndrome. With the MPS, it can cause a decrease in the functional ability of the neck. To overcome these disorders, the actions that can be given are in the form of progressive muscle relaxation exercises and McKenzie neck exercises, the purpose of giving a combination of ROP and McKenzie neck exercises is to increase the subjective experience that physiological tension can be relaxed, then restore normal neck alignment, and help reduce pain. So that it is able to provide an increase in the functional ability of the neck. Objective: To determine the effect of the combination of progressive muscle relaxation and McKenzie neck exercise on the functional ability of myofascial pain syndrome of upper trapezius muscle in college students. Research Methods: This study used a pre-experimental one group pretest and posttest with a total sample of 10 students who were given a combination of progressive muscle relaxation exercises and McKenzie neck exercise and carried out for 2 weeks a day 2 exercises. This study uses the Neck Disability Index as an instrument for measuring the functional ability of the neck. Research Results: The results of data analysis using the paired T-test showed a significance value of (0.000), therefore the P value <0.005, where H1 was accepted. Conclusion: There is an effect of a combination of progressive muscle relaxation and McKenzie neck exercise on increasing functional ability in cases of myofascial pain syndrome the upper trapezius muscle in KM HSS students in the Malang Region.